Antimicrobial Susceptibility Survey of Invasive Neisseria meningitidis, United States 2012–2016. (10th March 2022) - Potts, Caelin C; Rodriguez-Rivera, Lorraine D; Retchless, Adam C; Hu, Fang; Marjuki, Henju; Blain, Amy E; McNamara, Lucy A; Wang, Xin
Abstract: Background: Historically, antimicrobial resistance has been rare in US invasive meningococcal disease cases. Methods: Meningococcal isolates (n = 695) were collected through population-based surveillance, 2012–2016, and national surveillance, 2015–2016. Antimicrobial susceptibility was assessed by broth microdilution. Resistance mechanisms were characterized using whole-genome sequencing. Results: All isolates were susceptible to 6 antibiotics (cefotaxime, ceftriaxone, meropenem, rifampin, minocycline, and azithromycin). Approximately 25% were penicillin or ampicillin intermediate; among these, 79% contained mosaic penA gene mutations. Less than 1% of isolates were penicillin, ampicillin, ciprofloxacin, or levofloxacin resistant. Conclusions: Penicillin- and ampicillin-intermediate isolates were common, but resistance to clinically relevant antibiotics remained rare. Abstract : Antimicrobial susceptibility testing of 695 US meningococcal isolates, collected 2012–2016, demonstrated that penicillin- and ampicillin-intermediate isolates were common; resistance to clinically relevant antibiotics remained rare.